Identification of phosphorus index improvements through model comparisons across topographic regions in a small agricultural watershed in Vermont (USA). Issue 4 (20th June 2021) - Twombly, Cameron R.; Faulkner, Joshua W.; Collick, Amy S.; Easton, Zachary M.
Abstract: Many U.S. states require farmers to evaluate the risk of P loss from farm fields using P site assessment tools, such as the Phosphorus Index (P‐Index). The simplicity of the P‐Index allows for users with various backgrounds to utilize the tool; however, the P‐Index may be limited in its ability to reliably predict P losses across variable farm terrain, for instance where saturation‐excess runoff generation dominates. The objective of this study was to identify potential improvements that could be made to the Vermont P‐Index (VT P‐Index) by comparing VT P‐Index predictions of P loss with those of a model that considers topographic controls on P transport. Scenarios with varying P management strategies were developed and modeled for corn ( Zea mays L.) silage production fields in a small agricultural watershed (360 ha) located in Vermont using both the VT P‐Index and a modified version of the Soil and Water Assessment Tool (SWAT). Modeled outputs from both the VT P‐Index and SWAT were aggregated based on topographic index (TI) class and compared for the directional agreement of P risk assessments and relative annual average dissolved and particulate P losses. The P‐Index nutrient management recommendations gave higher P loss risk ratings than SWAT for 94% of the 120 unique scenario combinations simulated. Results from this study suggest that the VT P‐Index could improve its ability to support farm nutrient management planning by incorporating topographic controls on runoff production into its estimation of P transport. Core Ideas: Consideration of topographic factors can improve estimation of dissolved P loss in the VT P‐Index. Best management practice effectiveness can be increased in the VT P‐Index by accounting for VSA hydrology. Generally, the VT P‐Index resulted in a higher risk of P loss rating than SWAT‐VSA.